Material and method selection for efficient solid oxide fuel cell anode: Recent advancements and reviews. (26th September 2018) - Rafique, Muhammad; Nawaz, Huma; Shahid Rafique, M.; Bilal Tahir, M.; Nabi, G.; Khalid, N.R.
Summary: The energy crisis has reached to an alarming situation due to increase in population. To overcome the shortfall of energy, solid oxide fuel cell (SOFC) being cheap, clean, and efficient renewable energy source is getting attention for electricity generation. Out of the three main components as anode, electrolyte, and cathode; anode/fuel electrode is an important component of SOFC because it allows the flow of electrons via external circuit to cathode generating the electric current and hence requires high electrical conductivity. In this review, anode materials synthesized until now are reviewed and by careful analysis categorized on the basis of operating temperature, conductivity, electrode polarization resistance, and structure. This comparison and categorization will provide selection criteria for state‐of‐the‐art and highly efficient anode materials for SOFC. In addition, the synthesis methods have been reviewed on the basis of their pros and cons, which will further facilitate the researchers to select the best synthesis method so as to get optimized properties of materials. Abstract : Ceramic, composite, and hybrid materials can be used as efficient anodes in SOFCs. This review provides comparative analysis and division of anodes materials on the basis of operating temperature, electrode polarization resistance, conductivity, and structure can provide guidelines to scientists and researchers for selection of novel anodes with highest efficiencies. Critical comparison of different existing synthesis methods of SOFC anodes will enable the researchers to optimize the best synthesis method to achieve exceptional properties.